ANALISIS DAYA DUKUNG PONDASI DENGAN METODE REESE & WRIGHT (1977) DAN SKEMPTON (1966) - Yelvi; Dio Akbar Hakim; Tulus Sebastian Gerraldo (Jurnal Poli-Teknologi, 2023)
Bridge has a structural load from above which is supported by the foundation. The foundation has an important role to holding the load from the superstructure. Therefore, planning the foundation, the bearing capacity must be taken into account so the foundation should withstand the load. In the Bengkulu – Taba Penanjung toll access road construction project, bored piles are used. To determine the bearing capacity of the foundation, NSPT soil data is needed for analysis needs. Based on the results of the bearing capacity analysis, the value of 382 tons with the Reese & Wright method and 349 tons with the Skempton method at a depth of 14 m was obtained. With a 7 x 2 pile configuration, an average efficiency value of 85% is obtained. With this efficiency value, the group pile bearing capacity is 4538,22 tons (Reese & Wright) and 4147,47 tons (Skempton). With the group's pile bearing capacity, the pile is considered capable of withstanding the axial load of the superstructure of 2391.21 tons. The amount of immediate settlement that occurs in a single pile is 13.72 mm using the Vesic method (1977). This reduction is safe where the settlement limit is 65 mm according to Skempton and Mc Donald. Because the dominant soil is clay, the value of the decrease in primary consolidation that occurs is 5 mm. Thus, the drill pile foundation with a length of 14 meters and a total of 14 piles with a configuration of 7 x 2 piles can be said to be feasible and can withstand the axial load transmitted to the drill pile foundation.